Association of neutrophil-to-lymphocyte ratio with stroke morbidity and mortality: evidence from the NHANES 1999–2020 - Xin Xu; Guoqiang Zhang; Guoqiang Zhang; Guoqiang Zhang; Fei Liu; Fei Liu; Fei Liu; Jingwei Zheng; Jingwei Zheng; Jingwei Zheng; Zhijie Jiang; Zhijie Jiang; et al. (Frontiers in Medicine)
BackgroundStroke is closely linked to inflammation, with the neutrophil-to-lymphocyte ratio (NLR) emerging as a promising inflammatory marker. This study aims to investigate the association between NLR and both morbidity and mortality in stroke patients.MethodsData from the National Health and Nutrition Examination Survey (NHANES) 1999–2020 were analyzed, including adults with complete neutrophil and lymphocyte count records. Multivariate logistic regression was used to examine the relationship between NLR and both stroke morbidity and all-cause mortality. Restricted cubic spline regression was employed to assess potential nonlinearity in these associations. Subgroup analyses were performed to identify influencing factors.ResultsAfter adjusting for confounders, the adjusted odds ratios (ORs) and 95% confidence intervals (CIs) for stroke in the higher NLR quartiles, compared to the lowest quartile, were 1.28 (1.07–1.52) and 1.36 (1.12–1.65), respectively. The restricted cubic spline curve indicated a nonlinear positive association between NLR and stroke risk. Additionally, an elevated NLR was positively associated with an increased risk of all-cause mortality.ConclusionThe findings underscore the potential use of NLR in stratifying and predicting mortality risk in stroke patients, suggesting its relevance in clinical practice.